Transcriptome and DNA methylation changes modulated by sulforaphane induce cell cycle arrest, apoptosis, DNA damage, and suppression of proliferation in human liver cancer cells. (February 2020) - dos Santos, Patrick Wellington da Silva; Machado, Ana Rita Thomazela; De Grandis, Rone Aparecido; Ribeiro, Diego Luis; Tuttis, Katiuska; Morselli, Marco; Aissa, Alexandre Ferro; Pellegrini, Matteo; Antunes, Lusânia Maria Greggi
Abstract: Abnormal epigenetic alterations are one of the keystones of cancer development. Epigenetic targeting drugs have become a promising and effective cancer therapy strategy. However, due to the high toxicity and unclear mechanisms of action of these drugs, natural compounds that cause epigenetic modulation have also been studied. Sulforaphane (SFN) is a promising bioactive compound for epigenetic targeting therapy. In this study, we investigate the effects of SFN on gene expression and DNA methylation in human hepatocellular carcinoma cells (HepG2). Using high throughput technologies in combination with cell-based assays, we find SFN is a potent anticancer agent, as it induces DNA damage, mitotic spindle abnormalities followed by apoptosis and proliferation inhibition in HepG2 cells. Our results show the upregulation of DNA damage response and cell cycle checkpoint genes. Also, we find the downregulation of cellular pathways frequently overexpressed in human cancer. As expected, SFN exerts epigenetic modulation effects by inhibiting histone deacetylases (HDACs). SFN might affect the activity of oncogenic transcription factors through methylation of its binding sites motifs. Our findings offer insights into SFN chemopreventive molecular effects in HepG2 cells and highlight SFN as a valuable natural approach to cancer therapy for future investigation. Highlights: Sulforaphane upregulated DNA damage response and cell cycle checkpoint genes. The CDK1 and cyclin B1 complex was upregulated and induced mitotic blockage. Sulforaphane inhibited HepG2 proliferation by downregulating MAP kinases. Sulforaphane modulated DNA methylation of binding sites of transcription factors.